2020
DOI: 10.1186/s42155-020-00153-y
|View full text |Cite
|
Sign up to set email alerts
|

Vascular anomalies: special considerations in children

Abstract: The diagnosis and treatment of vascular anomalies are a large part of the caseload for paediatric interventional radiologists. Although many of the principles of sclerotherapy and embolisation are the same in adult and paediatric practice, there are some key differences in the approach for children, including some longer term thinking about managing these chronic diseases and their impact on a growing child. Vascular tumours are not often seen in adult IR practice and the rarest can be life threatening; knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…[14][15][16] A primary reason for such low exclusion from systemic venous outflow rates of type 3 and 4 malformations stems from these malformations possessing draining veins of larger caliber that allow sclerosants to embolize into the central venous system, thereby limiting an operator's ability to safely achieve complete sclerosis of such lesions. 17 Li et al recently reported a 70% efficacy following combined ethanol and n-butyl cyanoacrylate sclerotherapy of their cohorts' Puig type VMs, higher than 55% curative rates previously reported in the literature. 18 The aim of sclerotherapy is to induce mural irritation of its respective target with subsequent sclerosis, collapse, and eventual pruning of the malformation.…”
Section: Discussionmentioning
confidence: 79%
“…[14][15][16] A primary reason for such low exclusion from systemic venous outflow rates of type 3 and 4 malformations stems from these malformations possessing draining veins of larger caliber that allow sclerosants to embolize into the central venous system, thereby limiting an operator's ability to safely achieve complete sclerosis of such lesions. 17 Li et al recently reported a 70% efficacy following combined ethanol and n-butyl cyanoacrylate sclerotherapy of their cohorts' Puig type VMs, higher than 55% curative rates previously reported in the literature. 18 The aim of sclerotherapy is to induce mural irritation of its respective target with subsequent sclerosis, collapse, and eventual pruning of the malformation.…”
Section: Discussionmentioning
confidence: 79%
“…63 Sclerotherapy of challenging, extensive macrocysts (e.g., frequently seen in neonatal cervicofacial or in mesenteric lesions) can be performed in use of pigtail drains with multiple sideholes inserted during the first treatment, which allows serial procedures over subsequent days while the children are awake. 18 A small part of LMs shrink spontaneously in the first months after birth; in these asymptomatic, young babies, delay of intervention can be adequate. In case of indications for treatment immediately after birth, the aim should be to shrink the LMs to enable the child to move head and feed to put on weight before elective surgery some months later.…”
Section: Interventional Treatment Optionsmentioning
confidence: 99%
“…In cooperation with the other clinical disciplines involved, as pediatrics, pediatric surgery, visceral surgery, ENT, plastic surgery, urology, and hemostaseology, an optimal and comprehensive treatment concept can be designed, in which each specialist contributes its relevant expertise. 18 This review aims to highlight the detailed clinical presentation of the different subtypes of venous (VM), lymphatic (LM), and arteriovenous malformations (AVM), as well as the corresponding interventional treatment options including radiation dose limitations and procedure-related side effects while considering the specificities related to pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is immensely gratifying to see four recent papers in this journal dedicated to paediatric interventional radiology (PIR) (Patel and Cahill 2021 ; Gill and Shivaram 2020 ; Gibson and Barnacle 2020 ; Shaikh and Gomez Munoz 2021 ). They detail the latest evidence for a range of complex interventions in children, demonstrating where best practice lies in this highly specialised field.…”
mentioning
confidence: 99%
“…The paper by Gibson and Barnacle emphasises some intriguing differences in the management of vascular anomalies in adults and children (Gibson and Barnacle 2020 ). Their paper gives due focus to vascular tumours which are far rarer and less consequential in adults but which can be life-threatening in the first few days of life.…”
mentioning
confidence: 99%